Things We've Learnt About Digital Possessions - Sellen, Abigail; Taylor, Alex; Banks, Richard; Lindley, Siân (Things We've Learnt About, 2014)
“Things We’ve Learnt About..” is a regular publication from the Socio-Digital Systems team that summarises our work around a specific theme in a way that we hope is interesting, insightful and inspirational. And most importantly, succinct.